Deubiquitinase inhibitor PR-619 reduces Smad4 expression and suppresses renal fibrosis in mice with unilateral ureteral obstruction. - Kotaro Soji; Shigehiro Doi; Ayumu Nakashima; Kensuke Sasaki; Toshiki Doi; Takao Masaki (PLoS ONE, 2018)
Deubiquitinating enzymes (DUBs) remove ubiquitin from their substrates and, together with ubiquitin ligases, play an important role in the regulation of protein expression. Although transforming growth factor (TGF)-β1-Smad signaling is a central pathway of renal fibrosis, the role of DUBs in the expression of TGF-β receptors and Smads during the development of renal fibrosis remains unknown. In this study, we investigated whether PR-619, a pan-DUB inhibitor, suppresses fibrosis in mice with unilateral ureteral obstruction (UUO) and TGF-β1-stimulated normal rat kidney (NRK)-49F cells, a rat renal fibroblast cell line. Either the vehicle (dimethyl sulfoxide) or PR-619 (100 μg) was intraperitoneally administered to mice after UUO induction once a day for 7 days. Administration of PR-619 attenuated renal fibrosis with downregulation of mesenchymal markers, extracellular matrix proteins, matrix metalloproteinases, apoptosis, macrophage infiltration, and the TGF-β1 mRNA level in UUO mice. Although type I TGF-β receptor (TGF-βRI), Smad2, Smad3, and Smad4 protein expression levels were markedly increased in mice with UUO, administration of PR-619 suppressed only Smad4 expression but not TGF-βRI, Smad2, or Smad3 expression. PR-619 also had an inhibitory effect on TGF-β1-induced α-smooth muscle actin expression and reduced Smad4 levels in NRK-49F cells. Our results indicate that PR-619 ameliorates renal fibrosis, which is accompanied by the reduction of Smad4 expression.